Myopic refractive shift represents dense nuclear sclerosis and thin lens in lenticular myopia. (23rd May 2013) - Cho, Yang Kyung; Huang, Wei; Nishimura, Eiichi
Abstract : Background: It is not rare to meet unilateral nuclear sclerotic cataracts with myopic refractive changes (lenticular myopia) compared with the fellow eye in the ophthalmic examination of patients with decreased visual acuity. To determine the relationship between the myopic refractive changes and interocular differences of parameters, we investigated the interocular differences of ocular parameters between a lenticular myopic eye and the fellow eye. Method: This retrospective study included 68 eyes of 34 patients, who showed unilateral lenticular myopia. We compared the dimensions of ocular component, such as anterior chamber depth, anterior chamber volume, lens thickness, vitreous chamber depth, lens position, lens density of nuclear sclerosis, anterior lens curvature and myopic refractive changes (spherical equivalent refraction) between the lenticular myopic eye and the myopic refractive change were examined. Results: Statistically significant differences were found between the lenticular myopic eye and the fellow eye for anterior chamber depth (p = 0.015) anterior chamber volume (p = 0.031), lens thickness (p < 0.001), lens density of the nuclear sclerosis (p < 0.001) and the spherical equivalent myopic refractive changes (p < 0.001). Based on univariate analysis, the interocular difference in spherical equivalent refraction was significantly correlated with interocular differences of the density of the nuclear sclerosis (r = 0.79, p < 0.001), lens thickness (r = ‐0.70, p < 0.001) and vitreous chamber depth (r = 0.43, p = 0.012). Based on multiple regression analysis, the interocular difference in spherical equivalent refraction was significantly correlated with interocular differences of density of nuclear sclerosis (p < 0.001) and lens thickness (p = 0.007). Conclusion: The difference in myopic spherical change reflects the differences in the severity of nuclear sclerosis and lens thickness between the lenticular myopic eye and the fellow eye.